Challenges and Implementation of Universal Health Coverage Program in Indonesia - Naufal Rizky Perdana; Gayatri Adhasari; Erlina Puspitaloka Mahadewi (CV. Inara, 2022)
The existence of Universal Health Coverage (UHC) implementation means that everyone in Indonesia will have access to the health services they need, when and where they need it, without financial hardship. It covers a wide range of essential health services, from health promotion to prevention, treatment, rehabilitation and miscellaneous care. Many countries are already making progress towards UHC, although the ubiquity of the global covid-19 pandemic is impacting the availability of health systems' ability to provide undamaged healthcare. All countries can take action to move more quickly towards UHC despite the setbacks caused by the pandemic, or to maintain the gains they have made. Indonesia continues to strive to realize Universal Health Coverage (UHC) through the implementation of the National Health Insurance-Healthy Indonesia Card (JKN-KIS) program whose program has been implemented by the government since 2014. Since the enactment of the policy on providing health services for the community through the National Health Insurance and the Healthy Indonesia card (JKN-KIS) by the Government, there have been more than 40 million people who have not been registered as participants in the National Health Insurance-Healthy Indonesia Card (JKN-KIS) program. This study uses a qualitative method by making a literature review with the aim of making it affordable for those whose health has not been protected through JKN-KIS services. As a recommendation in efforts to accelerate the achievement of UHC, the government must be committed to reducing the level of inequality between provinces and regions as well as regions in Indonesia, by building better health infrastructure and facilities, including a more even distribution of health workers in provinces with a UHC service coverage index that is still low.